(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In recent years learning foreign languages especially the English language is becoming popular, toddlers and adults are trying to speak in English. It is a growth that learning languages is not only speaking another language it is also getting information about culture, history, and customs of acquiring language. In addition, it can help to open the doors to the world.As a teacher, I have been asked by several students “how much time does it take to speak English?” or “After What Time Can I speak fluently?” They are common questions that all starters give every time. My answer always is it is up to individuals. I have a strong position that learners try to learn foreign languages from authentic materials even they do not understand fully. Although they watch or listen to real materials without comprehending, they learn how to pronounce the words and attitude toward the language.Moreover, using authentic material can give motivation to learn or to achieve their goals with the help of learning languages because learners attempt to look like a native and also speak as they do. When it comes to using authentic materials in the classroom can be useful as learners do not get stress from the traditional grammar-translation method, that is to say, they acquire the language more naturally than they did before, and as a consequence, they feel that language environment. On the other hand, there is an argument to be discussed, using authentic materials also choose the age and level. The present study aims to focus on the importance and as well as for what level can be used the authentic materials in foreign language learners.